Pengaruh Program Pemutihan Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Pada Kantor SAMSAT Kabupaten Bandung II Soreang - Wati, Rinda; Saepuloh, Cepi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The vehicle tax amnesty program is a policy implemented by local governments to improve vehicle taxpayer compliance by eliminating penalties and providing tax relief. This study aims to analyze the effect of the vehicle tax amnesty program on vehicle taxpayer compliance at the SAMSAT Office of Bandung Regency II Soreang. This research employs a quantitative method with a associative approach. Data was obtained through questionnaires distributed to 100 registered vehicle taxpayers at the SAMSAT Office of Bandung Regency II Soreang. Data analysis was conducted using simple linear regression to examine the relationship between the vehicle tax amnesty program as an independent variable and taxpayer compliance as a dependent variable. The results show that the vehicle tax amnesty program has a positive and significant effect on taxpayer compliance. The coefficient of determination (R²) value of 27.7% indicates that the tax amnesty program explains 27.7% of the variance in taxpayer compliance, while the remaining 72.3% is influenced by other factors. However, the study also found the potential for moral hazard, where taxpayers tend to delay tax payments in anticipation of future amnesty programs.